The effect of communicative activities on EFL learners’ motivation: a case of students in the Amazon region of Ecuador - Ochoa, César; Cabrera, Paola; Quiñónez, Ana; Castillo, Luz; González, Paúl (Colombian Applied Linguistics Journal, 2016)
This study sought to shed light on the relationship between communicative activities and their impact on students’ motivation to learn English as a Foreign Language (EFL). A total of 180 senior high school learners (86 male and 94 female) and 8 EFL teachers in a town of the Amazon region of Ecuador completed a questionnaire. A sample of these students and all of the teachers participated in a face-to-face interview. Both instruments were applied to obtain data concerned with use of communicative activities in the classroom and their relation with motivation. The data gathered was analyzed using a mixed-method approach, comprising quantitative and qualitative methods. Results showed that students and teachers believe that communicative activities are motivating. Furthermore, students feel highly motivated when participating in communicative activities because these enhance their fluency, pronunciation, and performance in the use of English in a realistic and enjoyable way since students are confident when they help each other during interaction in activities.